International Remittances and the Labour Market in Peru - Nuñez, Roy (2024)
International remittances are a relevant source of income in developing countries, with important implications for the labour market of recipient countries. Peruvian international migration is a particular case of Latin America, since it tends to be concentrated in middle-and high-income households and in highly educated people, who display particular preferences in relation to the labour market. Using data from 2004 to 2019, we analysed the impact of remittances on employment, hours worked, and wages of Peruvian workers. Our results show that remittances reduce labour participation by 9.8 percentage points (pp). On average, the effect is greater among dependent workers than self-employed workers (-7.5 pp versus -3 pp). Similarly, we observed an increase in hourly income in both types of work (10.1% and 65%, respectively). In this sense, the Peruvian case offers a new perspective on the effect of remittances on the labour market, where despite having most of its labour force in informal jobs and self-employment, it does not encourage employment in those sectors, as occurred in previous studies.